Depression and Suicidal Ideation among Transgenders - Izna Munir Slatch, Muhammad Munir Ahmed, Farzeen Mubarak, Izna Munir Slatch, Muhammad Munir Ahmed, Farzeen Mubarak (Journal of Rawalpindi Medical College, 2018)
Background:To study the frequency of depression and suicidal ideations among adult trans-gender individuals. Methods:It was a cross-sectional and descriptive study. Data was obtained from snow ball sample of transgender individuals. An informed consent explaining the procedure and purpose of study and assuring the confidentiality was taken. Data were collected in two phases. In phase I, 60 transgender individuals were screened by using two questionnaires (Hamilton Rating Scale for Depression and Beck’s Scale for Suicidal Ideation) and in phase II, 7 interviews were conducted to gather the qualitative data. Results: Five percent had mild depression, 18% showed moderate Depression, 37% severe depression and 40% were found having very severe depression. High tendency of suicidal ideation was found in 48%. Forty percent depicted higher suicidal desire and 60% expressed having a low suicidal desire. Conclusion: Majority of the transgender individuals reported having severe depression and suicidal ideations. Results suggested the positive correlation between depression and suicidal ideation.